2020
DOI: 10.1016/j.triboint.2019.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in rolling-sliding wheel/rail contact condition during running-in

Abstract: The risk of wheel-climb derailment increases if the traction coefficient in the wheel/rail contact is too high. This has been observed to happen more frequently just after wheel machining. This work investigates how the traction coefficient rises with evolution of the wheel/rail interface during the running-in. Experiments were performed using a fullscale wheel/rail contact rig and an ultrasonic array transducer mounted in the rail. Results were used to determine the stiffness of the contact interface. Contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Full-scale tests [18] found that smooth wheel on rough rail (case 1) was associated with a lower coefficient of friction than rough wheel on smooth rail (case 2). Tests were carried out at 3% slip with a Hertzian stress calculated to be about 1.3 GPa.…”
Section: 2mentioning
confidence: 95%
See 2 more Smart Citations
“…Full-scale tests [18] found that smooth wheel on rough rail (case 1) was associated with a lower coefficient of friction than rough wheel on smooth rail (case 2). Tests were carried out at 3% slip with a Hertzian stress calculated to be about 1.3 GPa.…”
Section: 2mentioning
confidence: 95%
“…The presence of a relationship between roughness and friction coefficient would facilitate simulations of accidents and will aid in avoiding them. This will be done by taking replicas of the wheel and rail's surfaces during the experiments and measuring their roughness afterwards (for details of a similar process see [18]). Further measurements would be done for the mass loss during the testing to identify how WEL affects the wear mechanism.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…With flange climb derailment which can typically occur when vehicles are running through turnouts and sharp curves, efforts are underway to develop methods for clarifying wheel/rail frictional behavior in the initial stages following wheel grinding to determine the cause of flange climb derailment (Fig. 5) [4]. While wheel and rail surfaces both appear nearly smooth, up close they have minute dents and bumps.…”
Section: Clarification Of Deterioration Mechanismsmentioning
confidence: 99%
“…3 (b). 14,15 The wheel-rail contact was assumed to be a single-point contact, and the contact point was located between the wheel tread and the rail head. The track model employed the ballastless track structure, which had the characteristics of strong stability, high smoothness and less maintenance, and is widely used in railway lines, especially in the high-speed rail.…”
Section: Finite Element Model Of Wheel-rail Transient Rolling Contactmentioning
confidence: 99%